Grammar for teachers: A guide to American English for native and non-native speakers - DeCapua, Andrea (Springer, 2014)
The purpose of Grammar for Teachers is to encourage readers to develop a solid understanding of the use and function of grammatical structures in American English. It approaches grammar from a descriptive rather than a prescriptive approach; however, throughout Grammar for Teachers differences between formal and informal language, and spoken and written English are discussed. Grammar for Teachers avoids jargon or excessive use of technical terminology and reviews essential grammar structures clearly and concisely." "The text encourages users to tap into their own, often subconscious, knowledge of English grammar and to make it a conscious knowledge they can apply to their own varied teaching settings. Grammar for Teachers emphasizes grammar from the perspective of learners of English, an approach that allows teachers to better appreciate the language difficulties learners of English face in ESL or mainstream classrooms. Discussions of areas of difficulties for learners of English are included throughout the text.